Issues and challenges of using CALL in learning Arabic: considerations for content development - Ahmed Mukhtar, Ibrahim Suliman; Sahrir, Muhammad Sabri; Hassan, Fekri Abidin (Center for Promoting Ideas (CPI), USA, 2013)
The objectives of this research are to introduce Computer Assisted Language Learning (CALL) scholars and their activities to the Arabic readers, provide the Arabic readers with many issues of CALL, introduce CALL journals to our teachers as well as to our students in IIUM and the Arabic readers, provide our teachers as well as our students in IIUM with CALL organizations, provide our teachers as well as our students in IIUM with latest CALL information and books, introduce CALL conferences information to our teachers as well as to our students in IIUM and the Arabic readers. The researchers designed questionnaire with eleven items about CALL issues e.g. (the future of CALL, CALL status at present, methodology of CALL, CALL and research, the theoretical framework of CALL, the development of CALL materials, the opportunities for training CALL teachers and the CALL in the third world as well as the CALL scholars’ comments and suggestions). The researchers sent this questionnaire to CALL scholars for their responses. The researchers used their opinions and suggestions after analysing their responses. The significant of this research are based on the researchers’ knowledge there is no other researchers dealing with Computer Assisted Language Learning in Arabic language, provides suggested Arabic CALL curriculums and guidelines to our teachers as well as our students in IIUM in designing Arabic CALL lessons and CALL curriculum, provide guideline to our teachers as well as students in IIUM in designing criteria of Arabic CALL evaluation. This research is also assisting our Arabic CALL teachers in CALL research as well as providing many articles and it is also reviewing CALL programs. The development of CALL material relates very much on education systems; an enhanced understanding of language pedagogy, each country’s education policies and resources. Training teachers is fundamental, but often neglected due to time and cost factors, computers will be used, but without a cogent argument to state that they improve the situation, administrators and policy makers will be hard pressed to justify additional expenses. Word-processing is still the most common application in CALL. The problem then as now knows enough about the technology and pedagogy to integrate the two effectively (see Ahmed , 2002b).